Reaksi Investor Pasca Pengumuman Indeks Idx High Dividen 20 - Meita Rahmawati; Patmawati Patmawati; Christian Damar Sagara Sitepu (Owner : Riset dan Jurnal Akuntansi, 2025)
The capital market is an attractive investment instrument for investors who want to profit from stock price movement. One of the indices that is quite popular in the capital market is the Idx High Dividend 20 Index. The announcement of the Idx High Dividend 20 Index is thought to influence investor behavior and result in significant changes in stock price and stock trading volume. This study is an event study that aims to empirically test the differences in abnormal returns and volume of stock trading activity before and after the announcement of the Idx High Dividend 20 Index. This study is a quantitative study. The results showed that the Asymp sig (2 Tailed) abnormal return was 0.086>0.05, so H1 which was left was rejected, which means there was no significant difference in the abnormal stock return value before and after the announcement. However, the statistical results showed that the average value of the volume of stock trading activity after the announcement of the Idx High Dividend 20 Index increased to 1.73540 and was supported by the results of the ranking test, there were 182 data from 260 data or around 70% of the value after>after the announcement of the Idx High Dividend 20 Index with the Asymp Value. Sig (2-tailed) of 0.000,0.05. Based on this value, the accepted H2 means that there is a difference in the volume of stock trading activity before and after the announcement of the Idx High Dividend 20 Index.